Dyadic Developmental Psychotherapy : Essential Practices and Methods. - Becker-Weidman, Arthur (Rowman & Littlefield Pub. Group, 2010)
The pervasive effects of maltreatment on child development can be repaired when professionals use effective, empirically validated, and evidence-based methods. This book describes a comprehensive approach to treatment, Dyadic Developmental Psychotherapy, which is an evidence-based, effective, and empirically validated family based treatment. Therapists, social workers, residential treatment programs, psychologists, and child welfare professionals will find this book of immediate practical value. Professors teaching family-therapy, child-welfare, and child-treatment courses will find the book a.